Analisis Makna Cinta Abadi dalam Lirik Lagu Sekali Seumur Hidup Karya Lesti Kejora pada Kajian Semiotika Ferdinand de Saussure - Lidiya, Lidiya; Marini, Marini; Hagi Julio Salas (Lembaga Pengembangan Kinerja Dosen, 2025)
Songs are a form of symbolic communication that serves to convey emotional, moral, and cultural messages through beautiful and artistic language. In the context of communication, songs are not merely entertainment, but also a medium for representing meaning that reflects the social and cultural values ​​of society. This study aims to analyze the meaning of eternal love in the lyrics of the song